LAJJA GAURI’S LEGACY: FEMINIST PERSPECTIVES ON SPIRITUALITY AND GENDER RIGHTS - Hore, Suhas Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Lajja Gauri, an ancient lotus-headed goddess often associated with fertility and creation, is a potent symbol deeply embedded in the religious and cultural consciousness of India. Her iconography, with its overtly feminine form and birthing posture, historically depicted her as the embodiment of life-giving power. However, modern feminist scholars have reinterpreted this ancient symbol, viewing her not merely as a goddess of fertility but as an icon of female autonomy, empowerment, and spiritual purity. This paper explores the evolving symbolism of Lajja Gauri through the lens of contemporary feminist thought, connecting her image to broader discussions on gender equity, women’s rights, and the fight against gender-based violence. By examining how her iconography has been reclaimed by feminist movements, the study underscores the intersection of spirituality and gender within the context of modern struggles for social justice. Through an interdisciplinary methodology that combines art history, feminist theory, cultural studies, and comparative religious analysis, this research illustrates how the Lajja Gauri remains relevant as a powerful metaphor for female strength, autonomy, and spiritual authority. Ultimately, this study argues that ancient symbols like Lajja Gauri can inspire modern feminist movements, offering new pathways to challenge patriarchal structures and reaffirm the sacredness and autonomy of women’s bodies and identities in both spiritual and societal contexts.